Analysis of lipidomics profile of rice and changes during storage by UPLC-Q-extractive orbitrap mass spectrometry. (April 2021) - Zhang, Dong; Duan, Xiaoliang; Shang, Bo; Hong, Yu; Sun, Hui
Graphical abstract: Highlights: UPLC-Q-Exactive Orbitrap-MS lipidomic analysis method was employed. 21 subclasses, 277 individual lipids were identified in two rice varieties. Subclasses and individual lipids among fresh and stored rice were compared. 22 individual lipids showed significant difference between fresh and stored rice. The different lipids were involved in 3 most relevant metabolism pathways. Abstract: Rice is one of major staple food worldwide; however, lipid profile of rice and changes during storage remain unclear. Herein, an UPLC-Q-Exactive Orbitrap/MS method was applied for comprehensive lipidomics analysis of rice during storage. A total of 21 subclasses of 277 lipids including fatty acid (36 species), (O-acyl)-1-hydroxy fatty acid (6 species), diglyceride (16 species), triglyceride (89 species), lysophosphatidylcholine (4 species), phosphatidylcholine (14 species), phosphatidylethanolamine (28 species), phosphatidylglycerol (6 species), phosphatidylinositol (11species), cardiolipin (4 species), ceramide (8 species), hexosylceramide (20 species), dihexosylceramide (2 species), trihexosylceramide (1 species), sitosterol ester (1species), acyl hexosyl campesterol ester (5 species), acyl hexosyl sitosterol ester (6 species), digalactosyldiacylglycerol (6 species), monogalactosyldiacylglycerol (9 species), monogalactosylmonoacylglycerol (2 species), and sulfoquinovosyldiacylglycerol (3 species), were first identified in rice during storage. In addition, ceramide, fatty acid, (O-acyl)-1-hydroxy fatty acid, phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, lysophosphatidylcholine, and diglyceride were quantified. Furthermore, statistical analysis of all lipids was performed based on MetaboAnalyst software. The results showed that 22 lipids were significantly different between fresh and stored (360 and 540 days storage) rice demonstrating that lipid composition changed during storage. These different lipids involved 11 metabolic pathways, of which linoleic acid metabolism, glycerophospholipid metabolism, and cutin, suberine and wax biosynthesis were the most relevant. Our study provides useful information for lipidomics profile of rice during storage.